Parent Perspectives of Their Involvement in IEP Development for Children With Autism. (March 2020) - Kurth, Jennifer A.; Love, Hailey; Pirtle, Jody
The present study investigated parents' experiences in making educational decisions for their children with autism and their satisfaction with said outcomes. Parents completed a survey describing (a) their input in educational decisions, (b) satisfaction with school personnel, and (c) satisfaction with their child's school experience. Sequential regressions revealed parents' satisfaction was generally predicted by their own knowledge of autism, school staff knowledge of autism, parent satisfaction with teachers, and parent relationships with school personnel. In addition, parent input was a significant predictor of satisfaction with their child's school experience. Finally, open-ended responses indicated that parents experienced many barriers when working with schools and often felt compelled to go outside of the school system to ensure their children received an appropriate education. Implications for teacher preparation and school–parent partnerships are described.